AGRICULTURA FAMILIAR E FRUTICULTURA IRRIGADA: ESTUDOS DE CASO NO NORDESTE - Vital, Tales; Sampaio, Yony (Anais da Academia Pernambucana de Ciência Agronômica, 2014)
Experiences of inclusion of irrigated fruit farming in family farming in thenortheast of Brazil are analyzed. It’s highlighted the experience of CASI–Project for the Conservation of Water and Irrigation Systems, because it is apioneer project encompassing research and experimentation with theproducers. They are examined experiences of little impact, either singly or inprojects in irrigated areas, and successful experiences, again including specificactions and large areas. Based on the methodology, factors that may be relatedto the results are analyzed, which includes: the availability of water and insufficient quantity; the availability of energy sources for the distribution ofwater, the experience of producers with irrigated agriculture, the availabilityof irrigation technologies representing the different combinations of systemsand crops, the possibility of coordination and cooperation between theirrigators and, in particular, the achievement of economic results, for whichthe market plays a decisive role. Additionally, there are problems ofmismanagement and difficulties of linking the various components neededfor a project from the point of view of sustainable economic, social andenvironmental. In conclusion, the analysis shows necessary conditions andsuccessful experiences in consolidating the family farming in the Northeast.